From Design to Classroom: Developing a Generative-AI Enhanced Gamified Project-Based Civic Learning Framework - Bramantya, Alfan; Pujiati, Eko; Ikhwaningrum, Dian Utami; Kusuma, Reynaldi Arya Putera; Zuhro, Adinda Ni’matus; Soares, Marçal Vitor (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to developed and preliminarily evaluated a Generative-AI-supported gamified Project-Based Civic Learning (GPBL-Civ) framework to strengthen student engagement and creative performance. This study employed a research and development method using the ADDIE model (analysis, design, development, implementation, and evaluation), The study involved undergraduate Civic Education students and aimed to examine the feasibility and effectiveness of a gamified project-based civic learning strategy supported by generative AI. Data were collected using expert validation instruments and student assessment tools. Feasibility was evaluated by four experts across strategy and content dimensions using Likert-scale questionnaires aligned with course learning outcomes. Effectiveness was examined through a single-group pretest–posttest design in one Civic Education class. Student engagement was measured using a validated engagement scale, while creativity was assessed using rubric-based evaluations of student projects. Data analysis employed descriptive statistics and normalized gain (N-gain) to determine improvements in engagement and creativity. The results indicate that the Generative-AI-assisted gamified Project-Based Civic Learning framework was rated “feasible” to “very feasible” by expert validators assessing both strategy and content. Classroom try-out results showed moderate improvements in student engagement (average N-gain = 0.66) across behavioral, emotional, and cognitive dimensions. Student creativity also demonstrated meaningful gains (average N-gain = 0.68), as reflected in rubric-based assessments of originality, elaboration, and effectiveness. Overall, the findings suggest that the developed framework has strong potential to enhance student participation and improve the quality of project outcomes in Civic Education courses. The instructional package may serve as a practical classroom supplement for university instructors implementing project-based civic learning with responsible use of Generative AI.